1977
DOI: 10.3758/bf03199489
|View full text |Cite
|
Sign up to set email alerts
|

Processing of geometrical dimensions in a binary classification task: Evidence for a dual process model

Abstract: Confirming the findings in search tasks with letters and digits, the typical RT same < RTdiff result was obtained in a matching paradigm requiring the classification of geometrical stimuli that were given in pairs. The study supports a dual process model that is based on an identity reporter for the faster "same" response and a difference detector for the slower "different" responses, both operating with equal accuracy. Subjects appeared to perceive outline aspects of figures, formed by size and form, holistic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
25
0

Year Published

1978
1978
1995
1995

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(27 citation statements)
references
References 16 publications
2
25
0
Order By: Relevance
“…We now know that size of circle and tilt of diameter are nonintegral dimensions (Garner & Felfoldy, 1970), as are color and shape (Handel & Imai, 1972). Accordingly, Biederman's stimuli were at least partly nonintegral and thus might be expected to be processed an attribute (or object) at a time, just as were the attributes of Higgins and Getty's (1977) faces and some attributes of Keuss' (1977) geometric patterns. Consider, as an example, the first defined orthogonal task (called filtering) in Table 1 in Biederman's (1972) extensive classification study.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…We now know that size of circle and tilt of diameter are nonintegral dimensions (Garner & Felfoldy, 1970), as are color and shape (Handel & Imai, 1972). Accordingly, Biederman's stimuli were at least partly nonintegral and thus might be expected to be processed an attribute (or object) at a time, just as were the attributes of Higgins and Getty's (1977) faces and some attributes of Keuss' (1977) geometric patterns. Consider, as an example, the first defined orthogonal task (called filtering) in Table 1 in Biederman's (1972) extensive classification study.…”
Section: Discussionmentioning
confidence: 99%
“…In some studies responses are speeded if all attributes of a stimulus repeat and do so in the same configuration (identity), but responses are not speeded if some characteristic of the stimulus, an attribute or the configuration, is changed on successive trials (nonidentity) (Felfody, 1974;Keuss, 1977; the present paper). In other studies response times are facilitated both when there is identity repetition and when only some attributes repeat.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Any repetition of Keuss' (1977) study, it is suggested, should include both sequential and simultaneous stimulus presentation modes. (All other procedural details of the present investigation are identical to Keuss, 1977. For a rationale, a reference is made to that study.) The main assumption of the present study is that the use of a retention interval following the first, or memory, stimulus may facilitate subject's analytical approach.…”
Section: Free University Amsterdam the Netherlandsmentioning
confidence: 99%